PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MENGGUNAKAN MODEL INKUIRI TERBIMBING DI KELAS III SDN 01 BANDAR BUAT KOTA PADANG - Kurniawan, Afdal; Zuryanty; Ummiatul Fitri; Afriza Media (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Afdal Kurniawan. 2026. This classroom action research aimed to improve student learning outcomes in the Science and Social Studies (IPAS) subject through the Guided Inquiry model in Grade III of SDN 01 Bandar Buat, Padang City. The study was motivated by low learning outcomes, where only 9 of 29 students (31%) reached the minimum mastery criterion (KKTP), with a class average of 63.8, because the teacher previously applied an inquiry model using only four of its six syntax steps and left it too open for third-grade students who still needed structured guidance. The research employed a classroom action research design combining qualitative and quantitative approaches, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were the class teacher and 29 third-grade students (15 boys and 14 girls). Data were collected through observation sheets, teaching-module assessment sheets, and learning outcome tests, then analyzed descriptively using percentage formulas. The results showed that teaching-module quality increased from 82% in Cycle I to 96% in Cycle II, teacher activity rose from 84% to 94%, and student activity rose from 78% to 94%. Classical learning completeness reached 86% in Cycle II, with an average knowledge score of 84.8 and an average skill score of 96.6. These findings indicate that the guided inquiry model, applied with a complete six-step syntax and a stronger facilitative role for the teacher, effectively improves student learning outcomes in the IPAS subject in Grade III of SDN 01 Bandar Buat, Padang City.